(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Over the past 100 years, the number of laws governing road transport has grown, giving judges and lawyers a steady stream of work. There doesn’t seem to be any chance that the law will stay the same, since new offences and suggestions are made to improve road safety and keep people from getting hurt on the roads. But, as can be seen with speeding tickets, this good goal is often not understood by those to whom it applies. Education and better engineering of both roads and cars are also ways to reduce the damage caused by vehicles. The question is how far we can expect the law to go to achieve these goals and how to make crimes that are most likely to work. Why is it that the criminal law, and not some other part of the law, should try to stop bad driving behaviour on the road? Criminal law is different from civil law in that people who break criminal law are often made fun of in public. People who break civil law, on the other hand, may get fines, but they are generally not shamed in public for not following the law. A crime is not only against the person who was hurt, but also against the State as a whole. The State is in charge of taking people who break the law to court and punishing them for doing so. To figure out who should be punished, the State must decide ahead of time what kind of action should be made illegal and punished.